PERLINDUNGAN HAK MASYARAKAT HUKUM ADAT ATAS TANAH ADAT: STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 47 PK/PDT/2021 - Ilham Fajar Sayuti; M Sofyan Pulungan (Universitas Labuhanbatu, 2026)
This study aims to examine the legal validity of customary land sale and purchase transactions that result in the transfer of individual customary land rights to other parties and to analyze the legal protection afforded to indigenous peoples based on Supreme Court Decision Number 47 PK/Pdt/2021. The research employs a normative legal research method using statutory, case, and conceptual approaches. The study relies on primary legal materials consisting of legislation and court decisions, supported by secondary legal materials including books, scholarly articles, and legal doctrines, which are analyzed qualitatively through legal interpretation. The findings reveal that the disputed customary land transaction failed to satisfy the legal requirements of a valid agreement under Article 1320 of the Indonesian Civil Code because it was based on invalid legal documents, thereby rendering both the transfer of rights and the resulting certificate of ownership legally defective. Furthermore, the transfer of customary land rights did not comply with customary law, the Basic Agrarian Law, and the legal framework governing indigenous peoples in Papua. Supreme Court Decision Number 47 PK/Pdt/2021 demonstrates that legal protection for indigenous peoples extends beyond formal documentary evidence by recognizing customary law, historical possession, and local wisdom as important judicial considerations. This study contributes to the development of Indonesian land law by affirming the jurisprudential value of the decision in strengthening the protection of indigenous land rights and providing guidance for resolving future customary land disputes.Keywords: indigenous peoples; customary land; legal protection; individual customary rights; jurisprudence.